The Extinction of Desire : a Tale of Enlightenment. - Boylan, Michael (Blackwell Public Philosophy Series, 2007)
Michael O'Meara, a high school history teacher in Maryland, after a freak accident, finds himself the beneficiary of a million dollars. As friends, adversaries, and a greedy ex-wife emerge from the background to lay claim to the fortune, Michael finds himself caught up in a number of troubling situations. This work maps the course of his voyage.